Theoretical and experimental investigation of magnetic layer coupling in spin-valves and magnetic tunnel junctions - Gladczuk, L (2020)
Heterostructures composed of ferromagnetic layers that are mutually interacting through a nonmagnetic spacer are at the core of magnetic sensor and memory devices. In the present study, layer-resolved ferromagnetic resonance was used to investigate the coupling between the magnetic layers of a Co/MgO/Permalloy magnetic tunnel junction (MTJ) and Co/Sn/Py spin valves.